2017
DOI: 10.1007/s10096-017-2962-3
|View full text |Cite
|
Sign up to set email alerts
|

Current trends of human infections and antibiotic resistance of the genus Shewanella

Abstract: Shewanella spp. are commonly known as environmental bacteria and are most frequently isolated from aquatic areas. Currently, diseases syndromes and multidrug resistance have increasingly been reported in the genus Shewanella. Some species are associated with various infections, such as skin and soft tissue infections, as well as bacteremia. Generally, these bacteria are opportunistic and mostly affect people with an impaired immune system. This genus is also a probable vehicle and progenitor of antibiotic resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
68
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(69 citation statements)
references
References 70 publications
0
68
0
Order By: Relevance
“…Ambler Class D β‐lactamase OXA‐416 has been found in hospital wastewater isolated from carbapenem‐resistant S. xiamenensis (Yousfi, Touati, et al, ). The variants of bla OXA detected in S. xiamenensis also included bla OXA‐181 , bla OXA‐48b , bla OXA‐204 , bla OXA‐514 , bla OXA‐252 and bla OXA‐199 (Yousfi, Bekal, et al, ). Our data further suggest that aquaculture‐associated S. xiamenensis could be a potential source of class D β‐lactamase gene (Poirel, Potron, & Nordmann, ).…”
Section: Resultsmentioning
confidence: 99%
“…Ambler Class D β‐lactamase OXA‐416 has been found in hospital wastewater isolated from carbapenem‐resistant S. xiamenensis (Yousfi, Touati, et al, ). The variants of bla OXA detected in S. xiamenensis also included bla OXA‐181 , bla OXA‐48b , bla OXA‐204 , bla OXA‐514 , bla OXA‐252 and bla OXA‐199 (Yousfi, Bekal, et al, ). Our data further suggest that aquaculture‐associated S. xiamenensis could be a potential source of class D β‐lactamase gene (Poirel, Potron, & Nordmann, ).…”
Section: Resultsmentioning
confidence: 99%
“…In China, S. marisflavi caused high mortality in sea cucumbers (Li et al , ), and S. aquimarina was associated with a lesion syndrome of sea urchin (Wang et al , ). In shrimp, Shewanella species, and especially S. putrefaciens and S. baltica , were associated with spoilage of P. vannamei stored at low temperature (Qian et al , ; Qian et al , ; Zhu et al , ), and Shewanella species were also found to be a normal part of the bacterial flora in the P. vannamei gut (Suo et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…septicaemia, cellulitis, arthritis, otitis and pneumonia). Both are often recovered from mixed microbial flora of patients (Satomi, 2013;Yousfi et al, 2017). They have also been reported to be opportunistic pathogens in aquatic species.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations